Faktor-Faktor yang Mempengaruhi Kesuksesan Penerimaan Teknologi Sistem Informasi Manajemen Pemerintah dan Dampaknya terhadap Kinerja Karyawan (Studi pada Direktorat Jenderal Perbendaharaan) - Radiansyah, Rino; Surachman, Surachman; Sunaryo, Sunaryo (Jurnal Aplikasi Manajemen, 2016)
This study aimed to analyze the factors that affect the acceptability ofGovernment technology management information system and also to examine and analyze the impact of technology acceptance on employee performance, with job satisfaction as mediation. The factorare transformational leadership, systemquality,and facilitating conditions.The population in this study were 1872 people users SPAN at the Directorate General of the Treasury. Total sample were 240 users taken by simple random sampling techniques.This study were analyzed using descriptive analysis and Partial Least Square analysis (PLS).The results showed that the factors that affect the technology acceptance of SPAN aresystem quality and facilitating conditions, whereas transformational leadership has been unable to significantly affect the technology acceptance. The technology acceptance on employee performance successfully mediated by employee satisfaction, because that direct effect has not shown significant results.